Biological Method of Flyash Stabilisation through Afforestation on Ash Dump Yards near Thermal Power Station, Panki (Kanpur) - Srivastava, Ramjee; Kumar, Ashwani; Rai, A. M.; Singh, Lal (Indian Forester, 1995)
Rehabilitation offlyash dump yards through biological means has been tried at Panki Thermal Power Station, Kanpur. Ten tree species (Six nitrogen fixing and four non-nitrogen fixing) were tried under treated (50% soil of the pits replaced with normal soil and 2.0 kg of Farm Yard Manure + 150 gms of DAP) and untreated (control) conditions. Survival per cent, height and diameter were recorded every year. The results obtained in the third year show that the top performing species Udder treated conditions are Leucaena leucocephala, Acacia nilotica, Albizia lebbek and Pithecolobium dulce. The overall best performer under treatment was Leucaena leucocephala and without any treatment (Control) was Acacia nilotica. The top four performers under these two conditions happen to be nitrogen fixing. Therefore, it is suggested to rehabilitate the flyash dump yards with such type of nitrogen fixing tree species. It is further suggested to try more nitrogen fixing tree species so as to broaden the generalisation made in the present study.